A QR Code Used for Personal Information Based On Multi-Layer Encryption System - Haroon Rashid Hammood Al Dallal; Wijdan Noaman Marzoog Al Mukhtar (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Protecting and concealing sensitive data in the modern world is challenging. Due to insufficient protection and privacy, it is feasible for critical information to be fabricated. This led to a significant financial loss for someone. The intended recipient must be trusted with sensitive information and be able to independently authenticate the accuracy of the information by independently checking the specifics. There are several driving the rise in QR codes used for information transmission. Due to their enormous capacity for storing information, QR codes are vital for dissemination. However, most currently deployed QR code solutions employ insecure data formats and never employ encryption. Secure QR Code is data protection and data concealing available technology. The Quick Response (QR) code is widely used and accessible without extensive technical training. Now, the user data stored in a QR code is effectively public knowledge and occasionally even illegally used. To address the abovementioned issues, this study’s authors propose a novel QR code encryption system. Using the image’s mathematical processing method, we may apply the equivalence class principle to the ordered equations of the two-dimensional code, producing the desired cryptographic result. This method exploits the unique visual properties of the QR code. Only a QR code reader can decode the code’s useful information, which is too complex for standard reading methods. It will be utilised to address issues in speedy business client data protection Security, commodity anticounterfeiting, and bicycle sharing QR codes.